The Impact of Manufacturing Technology on the Tube-Steel Concrete Columns Bearing Capacity Under Axial Load - Evgenii M. Shcherban’; Alexey N. Beskopylny; Sergei A. Stel’makh; Levon R. Mailyan; Ivan A. Panfilov; Alexander L. Mailyan; Natalya Shcherban’; Ivan Vialikov; Diana Elshaeva; Andrei Chernilnik (Buildings)
Current construction puts forward new requirements for the construction of important buildings and structures every year. In this regard, new approaches to the design of buildings and structures using modern types of structural elements should take priority, which includes the vibrocentrifuged tube concrete columns. The purpose of this study is to evaluate the efficiency of manufacturing tube concrete columns using vibration (V), centrifugation (C), and vibrocentrifugation (VC) technologies and to perform a comparative analysis with the bearing capacity of solid tube concrete columns. Compositions of concrete grades B25, B30 and B40 were developed and manufactured using V, C and VC technologies. The greatest compressive strength was recorded for vibrocentrifuged concrete. Three samples of solid tube concrete columns and nine samples of hollow tube concrete columns were made from these concrete types. It was found that VC tube concrete columns have the highest bearing capacity values, which are up to 30.4% greater than those of vibrated columns, up to 15.1% greater than those of centrifuged hollow tube concrete columns, and up to 12.9% greater than those of vibrated solid tube concrete columns. It was proven that the use of vibrocentrifugation technology allows for the reduction in the weight of concrete pipe structures because of the hollow concrete core and the increase in the load-bearing capacity because of the high compression of the concrete core by the steel casing pipe.